Development of microextraction methods for the determination of sulfamethoxazole in water and biological samples: modelling, optimization and verification by central composite design - Amin, Issa Sheibani; Neysari, Ali Naser; Althomali, Raed H.; Musad Saleh, Ebraheem Abdu; Baymakov, Sayfiddin; Radie Alawady, Ahmed Hussien; Hashiem Alsaalamy, Ali; Ramadan, Montather F.; Juyal, Ashima (Frontiers in Environmental Science, 2023)
This study aimed to preconcentration of sulfamethoxazole (SMX) in water and biological samples. Ultrasound-assisted dispersive liquid-liquid microextraction (UA-DLLME) and ultrasound-assisted dispersive solid-phase microextraction (UA-DSPME) methods paired with spectrophotometry were applied to extraction and preconcentration of SMX. ZnFe2O4 nanoparticles were prepared as adsorbent in UA-DSPME method by hydrothermal method. The scanning electron microscopy (SEM) technique showed that the adsorbent had symmetrical, bullet-shaped particles with uniform size. The results of the X-ray diffraction (XRD) showed the successful synthesis of the ZnFe2O4 nanoparticles. Effective parameters in extraction, including ultrasonication time, disperser solvent volume, adsorbent amount, extraction solvent volume, eluent volume, and pH were investigated and optimized. The practical and optimal conditions of the process were determined by the central composite design (CCD). The optimal conditions were 0.024 g of adsorbent, 535 µL of disperser solvent volume, 7.5 min of ultrasonication time, 235 µL of eluent volume, pH of 5, and 185 µL of extraction solvent volume. Linear ranges and detection limits were 20-1200 μg L−1 and 6 μg L−1 for UA-DSPME and 10-800 μg L−1 and 3 μg L−1 for UA-DLLME. Relative standard deviation (RSD) of less than 4% were obtained for UA-DSPME and UA-DLLME methods. The reusability showed that the ZnFe2O4 adsorbent could extract SMX up to 5 cycles of adsorption/desorption without significant reduction in its efficiency. Also, interference studies showed that the presence of different cations and anions did not significantly interfere in the extraction of SMX. The outcomes of real-time samples analysis showed that the extraction of SMX for both methods was in the range of 92.44-99.12%. The results showed the developed methods are simple, sensitive, and suitable for SMX preconcentration in environmental water and biological samples.